The Benefits of Adding Sulfur and Urea to a Concentrate Mixture on the Utilization of Feed, Rumen Fermentation, and Milk Production in Dairy Cows Supplemental Fresh Cassava Root - Phussorn Sumadong; Sarong So; Anusorn Cherdthong (Veterinary Medicine International)
Fresh cassava roots that contain hydrocyanic acid (HCN) can be hazardous to animals when consumed. Prior literature has shown that adding sulfur may eliminate HCN without harming the health of animals. Additionally, adding urea is advised if sulfur was utilized since it helps with microbial protein synthesis. We thus proposed that supplementing the fresh cassava root diet with a high sulfur and urea in concentrate diet would be advantageous for rumen fermentation and milk production in animals. The purpose of this study was to see how high sulfur and urea levels in concentrate combinations affected feed utilization, rumen fermentation, and milk production in dairy cows fed diets including fresh cassava root. Four Holstein Friesian cows with 480 ± 50.0 kg BW, 10 ± 2 kg/head/day of milk yield, and 90 days in milk (DIM) were assigned at random in a 4 × 4 Latin square design with a 2 × 2 factorial design. Factor A was the concentration of sulfur in the concentrate diet at 10 g/kg and 20 g/kg dry matter (DM), while factor B was the concentration of urea in the concentrate diet at 10 g/kg and 20 g/kg DM. Fresh cassava root was given to each cow on a daily basis at a rate of 15 g DM/kg of BW. According to the findings, sulfur and urea had no interaction impact on feed intake, rumen fermentation, or milk production. Sulfur supplementation at 20 g/kg DM improved sulfur intake and digestibility of DM and organic matter much more than 10 g/kg sulfur. Additionally, sulfur supplementation at a dose of 20 g/kg DM in concentrate markedly increased blood and milk thiocyanate concentrations while lowering the somatic cell count. When compared to 10 g/kg DM urea, 20 g/kg DM urea significantly enhanced crude protein digestibility, ammonia-nitrogen concentration, blood urea nitrogen, and total volatile fatty acid concentration. Sulfur might detoxify hydrogen cyanide toxicity and be added at 20 g/kg DM in concentrate without harming the animals, whereas urea at 20 g/kg DM could increase feed digestion and rumen fermentation.